Application of concave induction cooking to improve the texture and flavor of braised pork - D. Da; C. Li (Теория и практика переработки мяса, 2022)
Long-term cooking may reduce the eating and nutritional quality attributes of meat products due to excessive oxidation. This study aimed to investigate the feasibility of concave induction to improve the quality of braised pork belly. Pork belly cubes were subjected to concave induction cooking (2000 W) or plane induction cooking (2000 W, traditional) for 60 min, 90 min, 120 min or 150 min. Then texture, fatty acid profile, lipid and protein oxidation, volatile flavor and sensory test in braised meat were evaluated. Compared with traditional method, concave induction cooking showed higher heating performance with shorter time to achieve a setting temperature. Compared with traditional cooking for 150 min, concave induction cooking for 60 min did not only produce a comparable volatile flavor and sensory scores, but also give better quality attributes, including lower hardness, chewiness, thrombogenicity values, PUFA/SFA value, lipid and protein oxidation. E‑nose results showed that samples cooked by concave induction for 60 min and 90 min showed a great similarity to those cooked by plane induction for 150 min. Concave induction cooking for 60 min also showed advantages to retain higher abundances of other volatile compounds including 2-pentylfuran, (E, E)-3,5-octadien‑2- one, 2, 3-octanedione, 2-decahydro‑1,6- dimethylnaphthalene when compared with plane induction cooking for 150 min.